Biochemical evidence that regulation of Ero1β activity in human cells does not involve the isoform-specific cysteine 262. Issue 2 (31st March 2014) - Hansen, Henning G.; Søltoft, Cecilie L.; Schmidt, Jonas D.; Birk, Julia; Appenzeller-Herzog, Christian; Ellgaard, Lars
Abstract : Our findings indicate that the regulatory disulfide bonds are conserved in the human oxidases Ero1α and Ero1β. We therefore propose that features other than a distinct pattern of disulfide bonds determine the previously established difference in regulation of Ero1α and Ero1β activity. Abstract : In the ER (endoplasmic reticulum) of human cells, disulfide bonds are predominantly generated by the two isoforms of Ero1 (ER oxidoreductin-1): Ero1α and Ero1β. The activity of Ero1α is tightly regulated through the formation of intramolecular disulfide bonds to help ensure balanced ER redox conditions. Ero1β is less tightly regulated, but the molecular details underlying control of activity are not as well characterized as for Ero1α. Ero1β contains an additional cysteine residue (Cys 262 ), which has been suggested to engage in an isoform-specific regulatory disulfide bond with Cys 100 . However, we show that the two regulatory disulfide bonds in Ero1α are likely conserved in Ero1β (Cys 90 –Cys 130 and Cys 95 –Cys 100 ). Molecular modelling of the Ero1β structure predicted that the side chain of Cys 262 is completely buried. Indeed, we found this cysteine to be reduced and partially protected from alkylation in the ER of living cells. Furthermore, mutation of Cys 100 –but not of Cys 262 –rendered Ero1β hyperactive in cells, as did mutation of Cys 130 . Ero1β hyperactivity induced the UPR (unfolded protein response) and resulted in oxidative perturbation of the ER redox state. We propose that features other than a distinct pattern of regulatory disulfide bonds determine the loose redox regulation of Ero1β relative to Ero1α.